THE INFLUENCE OF HUMAN RESOURCE MANAGEMENT BASED ON ISLAMIC VALUES AND TEACHER CERTIFICATION ON THE QUALITY OF EDUCATION AT MAN 2, PAREPARE CITY - Adyaksa, Adyaksa; Susilawati, Samsul; Esha, Muhammad In'am (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze and measure the influence of Islamic values-based Human Resource Management (HRM) and teacher certification on the quality of education at MAN 2 Parepare City. Methods: This research uses a quantitative approach with a survey method. The population was all 69 educators at MAN 2 Parepare, with a sample of 65 certified teachers taken using a census technique. Data were collected through a questionnaire that had been tested for validity and reliability. Data analysis techniques included descriptive statistics, classical assumption tests (normality, linearity, multicollinearity, heteroscedasticity), and multiple linear regression analysis. Results: The results showed that partially, Islamic values-based HRM had a positive and significant effect on the quality of education with t-count (4.596) > t-table (1.66980) and significance 0.000 < 0.05. Teacher certification also had a positive and significant effect with t-count (3.458) > t-table and significance 0.001 < 0.05. Simultaneously, both variables had a positive and significant effect on the quality of education with F-count (37.894) > F-table (3.15) and significance 0.000. The R Square value was 0.550, indicating that both variables explained 55% of the variation in education quality. Novelty: This research integrates Islamic values-based HRM and teacher certification in a single model, which has never been done in previous studies that examined both variables separately.